Inhibitor induced secondary recrystallization in thin-gauge grain oriented silicon steel with high permeability. (5th September 2016) - Fang, Feng; Zhang, Yuanxiang; Lu, Xiang; Wang, Yang; Cao, Guangming; Yuan, Guo; Xu, Yunbo; Wang, Guodong; Misra, R.D.K.
Abstract: Thin gauge grain-oriented (GO) silicon steel with high permeability was successfully processed by a simple way based on strip casting process, without hot rolling and decarburization annealing. The primary annealed sheet exhibited unique characteristics of homogeneous precipitation because of near-rapid solidification, and fine-grained recrystallized microstructure with relatively strong Goss texture and pronounced {111} 〈112〉 texture, which was responsible for the subsequent Goss abnormal growth. MnS, (Nb, V)N and AlN precipitates provided strong pinning effect on grain boundaries at different stages during the final annealing process, which is referred as "sequential inhibition behavior". The thin gauge GO silicon steel experienced complete secondary recrystallization induced by inhibitor, and exhibited sharp Goss texture together with significantly superior magnetic properties (magnetic induction B8  = 1.98 T; iron loss P1.7/50  = 0.7 W/kg). Graphical abstract: Highlights: Thin gauge grain-oriented silicon steel was produced by strip casting. High permeability was obtained by inhibitor-induced secondary recrystallization. The evolution of microstructure, texture and effect of inhibitor were elucidated. "sequential inhibition behavior" during the final annealing process is proposed.